تبني المقاولة الزراعية بمناطق الظل في الجزائر – دراسة استطلاعية لآراء عينة من الطلبة الجامعيين بمناطق الظل في ولاية عنابة - - العباسي, رمزي; سباع, أحمد الصالح (جامعة الوادي - University of Eloued, 2023)
هدفت الدراسة الحالية إلى التعرف على مستوى التوجه نحو المقاولاتية الزراعية من قبل الطلبة الجامعيين القاطنين بمناطق الظل في ولاية عنابة، ولتحقيق أهداف الدراسة الميدانية تم الاعتماد على المنهج الوصفي التحليلي، واستنادا عليه قمنا بتصميم استبانة وتوزيعها على عينة من (49) طالب جامعي بمناطق الظل، وتوصلت الدراسة إلى جملة من النتائج أهمها: وجود توجه مقاولاتي لدى الطلبة الجامعيين. The present study aimed to identify the level of adoption of agricultural entrepreneurship in shadow areas by studying the level of entrepreneurial orientation among university students from shadow areas in Annaba State, To achieve the objectives of the field study, we relied on the analytical descriptive approach and, based on this, we designed a questionnaire and distributed it to a sample of (49) university students in areas of shade, The study led to several results, the most important of which are: the existence of an entrepreneurial orientation among the university students under study.
Adoption of agricultural entrepreneurship in the shadow areas in Algeria An exploratory study of the opinions of a sample of university students in the shadow areas in the state of Annaba -
مقال
Keywords: التوجه المقاولاتي؛ المقاولاتية الزراعية؛ مناطق الظل.; entrepreneurial orientation; agricultural contracts; shadow areas